From corannulene to indacenopicene: Effect of carbon framework topology on aromaticity and reduction limits - Spisak, Sarah N.; Li, Jingbai; Rogachev, Andrey Yu.; Wei, Zheng; Papaianina, Olena; Amsharov, Konstantin; Rybalchenko, Alexey V.; Goryunkov, Alexey A.; Petrukhina, Marina A. (Organometallics, 2016)
The electronic structure, reduction limits, and coordination abilities of a bowl-shaped polycyclic aromatic hydrocarbon, indacenopicene (C26H12, 1), have been investigated for the first time using a combination of theoretical and experimental tools. A direct comparison with the prototypical corannulene bowl (C20H10, 2) revealed the effects of carbon framework topology and symmetry change on the electronic properties and aromaticity of indacenopicene. The accessibility of two reduction steps for 1 was predicted theoretically and then confirmed experimentally. Two reversible one-electron reduction processes with the formal reduction potentials at -1.92 and -2.29 V vs Fc+/0 were detected by cyclic voltammetry measurements, demonstrating the stability of the corresponding mono- and dianionic states of 1. The products of the doubly reduced indacenopicene have been isolated as rubidium and cesium salts and fully characterized. Their X-ray diffraction study revealed the formation of tetranuclear organometallic building blocks with the [M2(18-crown-6)]2+ (M = Rb (3) and Cs (4)) cations occupying the concave cavities of two C26H122- anions. The coordination of two outside exo-bound rubidium ions is terminated by crown ether molecules in 3 to form the discrete [Rb+4(18-crown-6)3(C26H122-)2] tetramer. In contrast, the larger cesium ions allow the 1D polymeric chain propagation in 4 to afford [Cs+2(18-crown-6)2(THF)(C26H122-)]∞.
CRIS-Team Scopus Importer:2023-03-20